Identification and comprehensive analysis of epithelial–mesenchymal transition related target genes of miR-222-3p in breast cancer - Fang, Yutong; Zhang, Qunchen; Chen, Chunfa; Chen, Zexiao; Zheng, Rongji; She, Chuanghong; Zhang, Rendong; Wu, Jundong (Frontiers in Oncology, 2023)
Background-Epithelial-mesenchymal transition (EMT) is a crucial mechanism that microRNA- 222-3p (miR-222-3p) promotes breast cancer (BC) progression. Our study aimed to identify EMT-associated target genes (ETGs) of miR-222-3p for further analysis of their roles in BC based on bioinformatics tools.Methods -Based on bioinformatics analysis, we identified ten core ETGs of miR-222-3p. Then we performed a comprehensive analysis of ten ETGs and miR-222-3p. Results -The expression of miR222-3p in Basal-like BC was significantly higher than in other subtypes of BC and the normal adjacent tissue. Pathway analysis suggested that the ETGs might regulate the EMT process via the PI3K-Akt and HIF-1 signaling pathway. Six of the ten core ETGs of miR-222-3p identified were down-expressed in BC, which were EGFR, IL6, NRP1, NTRK2, LAMC2 and PIK3R1. And SERPINE1, MUC1, MMP11 and BIRC5 were up-expressed in BC, which also showed potential diagnostic values in BC. Prognosis analysis revealed that higher NTRK2 expression and PIK3R1 expression were related to a better prognosis, and higher BIRC5 expression and miR-222-3p expression were related to a worse prognosis. Most ETGs and miR-222-3p were positively correlated with various infiltration of various immune cells and ICGs expression. Lower TMB scores were correlated with higher expression of MUC1 and NTRK2, and higher BIRC5 was related to a higher TMB score. Lower expression of MUC1, NTRK2 and PIK3R1 were associated with higher MSI scores. Higher expression of ETGs was associated with lower mRNAsi scores, except BIRC5 and miR-222-3p conversely. Most ETGs and miR-222-3p expression were negatively correlated with the drug IC50 values.The analysis of the genetic alteration of the ETGs suggested that amplification was the main genetic alteration of eight ETGs except for NTRK2 and PIK3R1.BCbiomarker to distinguish Basal-like BC from other subtypes. We successfully identify ten core ETGs of miR-222-3p, some might be useful diagnostic and prognostic biomarkers. The comprehensive analysis of ten ETGs and miR-222-3p indicated that they might be involved in the development of BC, which might be novel therapeutic targets for the treatment of BC. patients.